Transfusion Medicine Case Studies and Clinical Management - Mijovic, Aleksandar; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Transfusion Medicine: Case Studies and Clinical Management is an excellent way to illustrate current thinking about how to manage common transfusion medicine problems. The case studies and their accompanying commentaries provide a practical and enjoyable way to learn. Transfusion medicine emerged as a clinical discipline in its own right comparatively recently, having historically been a laboratory-based specialty. Its position among other clinical disciplines is peculiar; it belongs into haematology as much as into obstetrics; into surgery, or intensive care medicine, as much as into immunology; it has an important role in organ transplantation just as it does in acute trauma management. The physician specializing in transfusion medicine needs to understand the human body in its integrity, in health and in disease. Transfusion medicine is a holistic specialty par excellence. It also bridges the gap between the laboratory bench, where arcane serological problems can now be explained by means of molecular methods, and direct therapeutic application, such as in apheresis techniques. This book is recommended this book as a valuable resource to raise interest in the subject of transfusion medicine and, more importantly, improve the quality of care provided to patients.
Errare humanum est -- Send another sample, please -- Mosquito in the bag -- An enigmatic haplotype -- An unwanted passenger -- Persistent anaemia after haemopoietic cell Transplantation -- Acute reaction to red cells: what lies beneath? -- Dial M for haeMolysis -- Rash and hypotension during transfusion -- Breathless -- Regular transfusions, iron, and teenage pregnancy -- Woman with slurred speech and thrombo-cytopenia -- Strong tea or Coca Cola -- With a little help from friends -- Rare blood -- Who$1 (Bs the donor? -- The matchmaker -- The bruised newborn -- Learning from refusal -- The apheresis donor -- Heart of the matter -- Hepatitis in a man on haemodialysis -- A traumatic experience -- God bless the child.s
Keywords: Medicine; Blood transfusion; Hematology; Medicine & Public Health; Hematology; Blood Transfusion Medicine; Medicine/Public Health, general